2021
DOI: 10.1590/1518.8345.4466.3446
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of microbiota according to the type of birth: an integrative review

Abstract: Objective: to analyze scientific evidence regarding the relationship between the type of birth and the microbiota acquired by newborns. Method: this integrative review addresses the role of the type of delivery on newborns’ microbial colonization. A search was conducted in the Medical Literature Analysis and Retrieval System Online/PubMed and Virtual Health Library databases using the descriptors provided by Medical Subject Headings (MeSH) and Health Science Descriptors (DeCS). Results: infants born vaginall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 67 publications
2
29
1
2
Order By: Relevance
“…The development of neonatal gut microbiota is affected by several factors ( Bäckhed et al, 2015 ; Rutayisire et al, 2016 ; Kapourchali and Cresci, 2020 ; Vandenplas et al, 2020 ). Most early colonists in the gut of neonates are maternal, and the mode of delivery strongly affects the formation of the early gut microbiota in term infants ( Bäckhed et al, 2015 ; Rutayisire et al, 2016 ; Kapourchali and Cresci, 2020 ; Coelho et al, 2021 ). Studies have shown that vaginally-delivered neonates have more abundant Bacteroides , Bifidobacterium , and Lactobacillus ( Bäckhed et al, 2015 ; Rutayisire et al, 2016 ; Coelho et al, 2021 ), whereas neonates delivered by cesarean section (CS) are enriched in Staphylococcus , Streptococcus , and Clostridium ( Coelho et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of neonatal gut microbiota is affected by several factors ( Bäckhed et al, 2015 ; Rutayisire et al, 2016 ; Kapourchali and Cresci, 2020 ; Vandenplas et al, 2020 ). Most early colonists in the gut of neonates are maternal, and the mode of delivery strongly affects the formation of the early gut microbiota in term infants ( Bäckhed et al, 2015 ; Rutayisire et al, 2016 ; Kapourchali and Cresci, 2020 ; Coelho et al, 2021 ). Studies have shown that vaginally-delivered neonates have more abundant Bacteroides , Bifidobacterium , and Lactobacillus ( Bäckhed et al, 2015 ; Rutayisire et al, 2016 ; Coelho et al, 2021 ), whereas neonates delivered by cesarean section (CS) are enriched in Staphylococcus , Streptococcus , and Clostridium ( Coelho et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most early colonists in the gut of neonates are maternal, and the mode of delivery strongly affects the formation of the early gut microbiota in term infants ( Bäckhed et al, 2015 ; Rutayisire et al, 2016 ; Kapourchali and Cresci, 2020 ; Coelho et al, 2021 ). Studies have shown that vaginally-delivered neonates have more abundant Bacteroides , Bifidobacterium , and Lactobacillus ( Bäckhed et al, 2015 ; Rutayisire et al, 2016 ; Coelho et al, 2021 ), whereas neonates delivered by cesarean section (CS) are enriched in Staphylococcus , Streptococcus , and Clostridium ( Coelho et al, 2021 ). In our study, there was no difference in the alpha diversity of SGA neonates born by vaginal delivery and CS on days 1, 3, and 5, while the alpha diversity of SGA neonates delivered by CS showed a decreasing trend on day 7.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, in the last 40 years, there has been a marked increase in the number of surgical deliveries associated with high rates of preterm childbirth and prematurity with iatrogenicity (3,8) .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, in the world context, the debate about childbirth is marked by the effort to reduce the number of cesarean interventions and, at the same time, by the defense of the provision of qualified care to women ( 5 - 7 ) . In Brazil, in the last 40 years, there has been a marked increase in the number of surgical deliveries associated with high rates of preterm childbirth and prematurity with iatrogenicity ( 3 , 8 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation